COVID-19 CHALLENGES AND NEW LEARNING POSSIBILITIES AND REALITIES IN NIGERIA: PERSPECTIVES OF SOUTHWEST NIGERIA - Odiegwu-Enwerem, Chuks O. (African Journal of Social and Behavioural Sciences, 2024)
In the early 2020s, there was a noticeable large-scale transition to remote/distance learning by educational institutions and learners in Nigeria due to the COVID-19 pandemic. The pandemic restricted the movement of people, thereby affecting businesses, including education. Nevertheless, many people continue to learn through remote learning, also known as open and distance learning. This study examined the real and imagined difficulties associated with the transition to remote learning to establish institutional and individual responses to this new challenge. This was undertaken especially to determine how prepared these institutions and personnel were, the possible challenges inherent in remote learning, and the challenge of harmonizing and regulatory frameworks necessary for them to thrive in line with UNESCO‘s guidelines for operating ODL programs. The study adopted a qualitative approach in which in-depth personal interviews were used to generate data for analysis. Findings arising from answers to the interview questions in this study showed that knowledge of this pedagogy by critical stakeholders is quite high and can guarantee the required level of adoption among critical stakeholders. These findings indicate that the remote learning concept, although fairly new, has prospects for modifications, adaptations and proper guidelines from the appropriate quarters. The idea that stakeholders believe in the potential of remote learning to change the education trajectory is welcoming, as it has the potential to drive its implementation in the right direction.